Signature of mid‐Pleistocene lineages in the European silver fir (Abies alba Mill.) at its geographic distribution margin. Issue 16 (21st July 2021) - Scotti‐Saintagne, Caroline; Boivin, Thomas; Suez, Marie; Musch, Brigitte; Scotti, Ivan; Fady, Bruno
Abstract: In a conservation and sustainable management perspective, we identify the ecological, climatic, and demographic factors responsible for the genetic diversity patterns of the European silver fir ( Abies alba Mill.) at its southwestern range margin (Pyrenees Mountains, France, Europe). We sampled 45 populations throughout the French Pyrenees and eight neighboring reference populations in the Massif Central, Alps, and Corsica. We genotyped 1, 620 individuals at three chloroplast and ten nuclear microsatellite loci. We analyzed within‐ and among‐population genetic diversity using phylogeographic reconstructions, tests of isolation‐by‐distance, Bayesian population structure inference, modeling of demographic scenarios, and regression analyses of genetic variables with current and past environmental variables. Genetic diversity decreased from east to west suggesting isolation‐by‐distance from the Alps to the Pyrenees and from the Eastern to the Western Pyrenees. We identified two Pyrenean lineages that diverged from a third Alpine–Corsica–Massif Central lineage 0.8 to 1.1 M years ago and subsequently formed a secondary contact zone in the Central Pyrenees. Population sizes underwent contrasted changes, with a contraction in the west and an expansion in the east. Glacial climate affected the genetic composition of the populations, with the western genetic cluster only observed in locations corresponding to the coldest past climate and highest elevations. The eastern cluster was observed over a larger range of temperatures and elevations. All demographic events shaping the current spatial structure of genetic diversity took place during the Mid‐Pleistocene Transition, long before the onset of the Holocene. The Western Pyrenees lineage may require additional conservation efforts, whereas the eastern lineage is well protected in in situ gene conservation units. Due to past climate oscillations and the likely emergence of independent refugia, east–west oriented mountain ranges may be important reservoir of genetic diversity in a context of past and ongoing climate change in Europe. Abstract : Genetic diversity of the silver fir, Abies alba Mill., decreases from east to west in western Europe, suggesting isolation‐by‐distance from the Alps to the Pyrenees and from the Eastern to the Western Pyrenees. The two Western and Eastern north‐Pyrenean lineages identified diverged long ago, during the Mid‐Pleistocene Transition, while population size fluctuation occurred later, possibly during the Late Glacial Maximum, with a contraction in the west and expansion in the east. East‐west oriented mountains such as the Pyrenees are important reservoirs of genetic diversity in a context of climate change, making likely the emergence of independent refugia, lineages, and possibly local adaptation, needing conservation measures.